The Effectiveness of a Differentiated Process Teaching Module to Improve Students' Critical Reasoning Skills in the Context of Rational Numbers - Nani Ratnaningsih; Puji Lestari; Ali Kuswoyo (Program Studi Tadris Matematika Universitas Islam Negeri (UIN) Salatiga, 2025)
This study aims to examine the effectiveness of developing differentiated process learning modules on rational number material in improving students' critical reasoning skills. This study has a novelty in developing learning modules, namely by integrating process differentiation through the ADDIE (Analyze, Design, Development, Implementation, Evaluation) development model. This approach provides hope in adjusting the needs of diverse learners so that it has the potential to be more optimal in achieving learning objectives. The research method used is quantitative, with a one-group pretest-posttest design. The trial was conducted on 24 students at SMP Negeri Satu Atap 1 Kalipucang, Pangandaran Regency, West Java. The research instruments include student and teacher response questionnaires, as well as pretest and posttest tests to measure improvements in critical reasoning skills. The results of the study showed a significant increase in students' critical reasoning skills, with an average pretest score of 21.15 and a posttest score of 77.92. The average N-Gain value of 0.7279 (72.79%) showed a high increase in achievement. In addition, statistical analysis using a paired sample t-test with a p-value of 0.000 and an effect size of 5.831 proved that the differentiated process learning module had a very large impact on improving students' critical reasoning skills. The use of this module is effective because it not only improves learning outcomes but also encourages students to be more active in critical thinking through a more personalized and tailored learning approach. Thus, this learning module can be adopted by other educators as a tool to support more inclusive and effective learning in improving students' high-level thinking skills.